A feasibility study on the effects of Triton X-100 for the in vitro inactivation of Ebola virus on haematological assays. Issue 7 (15th December 2015) - Mifsud, Antoinette; Peelen, Daphne; Brincat, Patricia; Abela, Sylvana; Debattista, Neville; Laspina, Stefan; Zammit, Daniel; Camilleri, David J; Gatt, Alex
Abstract : Aims: The aim of this study was to check the effect of Triton X-100 on various, commonly used haematology test parameters. Methods: Anonymised blood samples were treated with 10 µL of 10% Triton X-100 per 1 mL of blood. Treated and untreated samples were tested in parallel for blood film morphology, complete blood counts (CBCs), flow cytometry, blood grouping and antibody screens. Samples were also taken in 3.2% citrate tubes for coagulation test analyses. Results: Statistical differences were noted in all CBC parameters apart from the mean cell volume, eosinophil and basophil counts. Platelet counts were significantly different with an apparent rise after the addition of Triton X-100. Samples were noted to have a high red cell fragmentation index. Immunological platelet counting methods using flow cytometry and fluorescent methods showed no significant differences and gave reliable results. Neither flow cytometry for T-cell subsets nor blood grouping/antibody screens were affected by Triton X-100. However, coagulation samples were severely haemolysed prohibiting analysis. Conclusions: We have demonstrated that the addition of Triton X-100 to haematology blood samples impacts mainly on platelet counts and coagulation studies due to haemolysis. The platelet count is spuriously raised probably due to the presence of red cell fragments. The latter can be circumvented by the use of immunological platelet counting technology.